Dantharsha- An Ayurvedic Approach - Kumar, Sumit; Thakur, Uma (International Research Journal of Ayurveda & Yoga, 2021)
Dantaharsha is a morbid sensitiveness of teeth, which affects all the people irrespective of age and sex. Person suffering from Dantaharsha (Sensitive teeth) cannot tolerate cold wind, they are unable to ingest food of various kinds such as sour, cold and hot, moreover experiences painful sensation in teeth. The approach of treatment in the form of fluorides, nitrates, lasers etc1 as desensitizers in modern science are not very satisfactory. Considering the above factors, an effective, less expansive, harmless and convenient treatment for Dantaharsha (Sensitive teeth) is essential. Various treatments have been explained to relieve Dantaharsha (Sensitive teeth) including Kavala (gargling), Gandusha (Oil Pulling), Dhuma, (herbal smoke inhalation) Nasya (Nasal medication therapy), Shirobasti (medicated/herbal oil with the help of a leather cap over the head), Yavagu (semi solid liquid), intake of Dugdha(milk) and Ghrita (ghee) etc.